2019
DOI: 10.2147/cia.s222655
|View full text |Cite
|
Sign up to set email alerts
|

<p>Wearable Technology To Reduce Sedentary Behavior And CVD Risk In Older Adults: A Pilot Randomized Clinical Trial</p>

Abstract: BackgroundPhysical exercise is associated with decreased cardiovascular disease (CVD) risk, but recent large-scale trials suggest that exercise alone is insufficient to reduce CVD events in high-risk older adults.PurposeThis pilot randomized clinical trial aimed to collect critical data on feasibility, safety, and protocol integrity necessary to design a fully powered randomized controlled trial (RCT) and evaluate the impact of combining structured exercise with an intervention designed to enhance non-exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Nineteen studies (Figure 1) 27‐45 were identified totaling 4937 participants (excluded studies with reasons for exclusion are available in Table ). Studies were conducted in three continents: 12 in North America, six in Europe and one in Oceania, and published between 2005 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies (Figure 1) 27‐45 were identified totaling 4937 participants (excluded studies with reasons for exclusion are available in Table ). Studies were conducted in three continents: 12 in North America, six in Europe and one in Oceania, and published between 2005 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Their proposal differs from usual telemetry systems by allowing for out-of-hospital monitoring through leveraging automatic detection algorithms and continuous home-to-hospital data. This level of healthcare decentralization is still largely hypothetical; however, a recent pilot study evaluated the effects of wearable activity trackers on physical activity amongst elderly patients at higher risk of CVD [47] . An ongoing prospective study by Lorenzoni et al is currently in the process of using a commercial smartwatch to address the lack of recovery trajectory data for TAVR/SAVR patients [48] .…”
Section: Resultsmentioning
confidence: 99%
“…Study staff provided each of the participants with personalized feedback on physical activity with tailored step count goals (10% increase per week with maximum increase of 800 steps per week to a maximum of 10,000 steps per week) and motivational messages via email. This physical activity prescription was based on the United States Preventive Services Task Force recommendations and protocols used in the general obesity and cardiovascular disease literature [ 10 , 11 ]. Patients with consecutive days without data recorded or with other signs of low Fitbit usage (days with minimal step counts) were contacted via email or phone to encourage increased use.…”
Section: Methodsmentioning
confidence: 99%
“…The design was based on a pre-existing study protocol that had been pilot-tested among individuals with cardiovascular disease and shown to be feasible and efficacious in that patient population. 10 All participants received a Fitbit Zip at enrollment to track step counts. Participants were to wear their FitBit every day during waking hours for the entire study.…”
Section: Lifestyle Interventionmentioning
confidence: 99%